The emerging role of GlycoRNAs in immune regulation and recognition - Montag, Nicole; Gousis, Pavlos; Wittmann, Jürgen (Immunology letters, 2025)
Glycosylation, the enzymatic attachment of glycans to biomolecules, is a vital post-translational modification that impacts protein stability, immune recognition, and cellular communication. Traditionally associated with proteins and lipids, recent discoveries have revealed the existence of glycosylated RNAs (glycoRNAs), expanding our understanding of RNA modifications. GlycoRNAs challenge conventional paradigms by suggesting that glycosylation may regulate RNA stability, localization, and interactions with glycan-binding proteins, such as sialic acid-binding immunoglobulin-type lectins (Siglecs) and selectins. These interactions are particularly significant in the immune system, where glycosylation plays a key role in antigen recognition, immune cell trafficking, and pathogen detection. The potential implications of glycoRNAs in immune regulation and disease are profound, with roles in autoimmune disorders, cancer, and infectious diseases. Advances in glycobiology, including mass spectrometry, RNA sequencing, glycan microarrays, and click chemistry technologies, are driving the growth of glycoRNA research and its translational applications. Understanding glycoRNAs could lead to new therapeutic opportunities, including glycoengineering, biomarker discovery, and targeted immune interventions. Despite challenges including low abundance and complex structure, research into glycoRNA is progressing rapidly, revealing their roles in immune responses and disease mechanisms. This review synthesizes the current knowledge on glycoRNAs, highlighting their emerging significance in immunology and outlining future research directions.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Glycan-binding proteins; GlycoRNA; Glycosylation; Immune regulation; Small RNAs